Urgensi Literasi Zakat Profesi Bagi Generasi Muda Muslim di Kelurahan Bonebone Kecamatan Betoambari Kota Baubau - Sudirman Sudirman (JURNAL HUKUM, POLITIK DAN ILMU SOSIAL, 2022)
Professional zakat is one form of zakat that holds great potential in improving community welfare, especially among the younger generation. In Bonebone Subdistrict, Betoambari District, Baubau City, literacy regarding professional zakat remains relatively low. This study aims to identify the urgency of professional zakat literacy for the young Muslim generation in the area. Using a qualitative method, data were collected through interviews and surveys. The results show that increasing professional zakat literacy can have a positive impact on the awareness and participation of young people in paying zakat.